Facile Synthesis and Characterization of Novel Fe0.65Mg0.35Cr2O4@C Nanocomposite for Efficient Removal of Cd(II) Ions from Aqueous Media - Ehab A. Abdelrahman; Reem K. Shah; Mortaga M. Abou-Krisha; Fawaz A. Saad; Alaa M. Munshi (Inorganics)
Cd(II) ions pose significant environmental and health threats due to their extreme toxicity, persistence, and bioaccumulation in ecosystems. They are associated with severe health disorders such as bone damage, kidney failure, and carcinogenic effects and disrupt aquatic life by impairing enzymatic and reproductive processes. In this research, novel Fe0.65Mg0.35Cr2O4@C nanocomposites, synthesized using the Pechini sol–gel method at 600 °C (F600) and 800 °C (F800), were investigated for their efficacy in removing Cd(II) ions from aqueous media. FE-SEM analysis showed that F600 had agglomerated spherical nanoparticles with an average grain size of 45.71 nm and a relatively porous structure, while F800 displayed denser and more compact spherical nanoparticles with an average grain size of 73.65 nm. HR-TEM images confirmed these findings, showing that F600 nanoparticles were loosely arranged with an average particle diameter of 14.72 nm, whereas F800 exhibited larger, more aggregated particles with an average diameter of 59.22 nm, reflecting enhanced particle coalescence at higher temperatures. EDX analysis confirmed the elemental composition of both samples, with F600 containing higher carbon content (7.0%) compared to F800 (3.4%), attributed to the more complete combustion of organic precursors during F800’s synthesis. This difference in composition, along with the structural variations, influenced their adsorption performance. F600 demonstrated superior adsorption with a maximum capacity of 295.86 mg/g compared to F800’s 185.19 mg/g. Thermodynamic and kinetic analyses confirmed that the adsorption was exothermic, spontaneous, and governed by a physical mechanism following the pseudo-second-order model and Langmuir isotherm. The superior performance of F600 is attributed to its higher surface area, porosity, and smaller particle size, which enhance the availability of active adsorption sites.